OVERCOMING THE REVERSE CULTURE SHOCK EXPERIENCE IN INDONESIAN CHILDREN OF DIPLOMATS FROM LIVING OVERSEAS DURING PRIMARY SCHOOL YEARS - Alita Mislia Salsabilla; Cyntia Keliat (Jurnal Scientia, 2023)
The failure to adjust back to their home country can give a psychological impact on an individual, including young adults. This paper aims to explore the Indonesian children of diplomats who overcame reverse culture shock. This paper employed qualitative approach by utilizing in-depth interviews as a data collection tool. Two young adults who experienced reverse culture shocks on their return after living abroad as children were purposively chosen as informants. The research applies two theories: Communication Accommodation Theory and Developmental Model of Intercultural Sensitivity that correlates in findings of research. Result showed their ability to communicate in various of different cultural frames and prospects which formed their capability to understand diversification.